SINERGI PENTAHELIX DALAM MENDORONG KEMANDIRIAN EKONOMI UMKM DISABILITAS TUNA NETRA DI KOTA DENPASAR - Ni Made Ayu Dwijayanti; I Gusti Ayu Astri Pramitari; Ni Made Mega Abdi Utami; M. Yusuf; I Wayan Karmana (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
This community service activity aims to promote the economic independence of blind disability MSME actors in Denpasar City through the Pentahelix model approach. This model involves five key elements: academia, business actors, the community, government, and media. The activity was conducted at the Teratai SME for the Blind Disability, using methods such as pre-surveys, field surveys, program implementation, and evaluation. The findings revealed that the main challenges faced by the SME partners include unstructured financial record-keeping, insufficient promotion, and limited market access. Academics played a role in developing an accounting application based on Microsoft Access for transaction recording in accordance with SAK EMKM standards. Businesses were supported through training and the creation of an online catalog to expand market reach. The community, through KUBE Gantari Jaya, facilitated training and product bazaars. The Denpasar City Government provided support through the provision of facilities and legalization of the disability-owned SME community. Pusaka Denpasar is a collaboration platform involving the government, partners, cooperatives, and SMEs to advance cooperatives and SMEs in the city of Denpasar. The Cooperative and SME Agency acts as a facilitator in providing legal and administrative documents, while collaboration partners play a role in mentoring through various cooperation programs. Social media and mass media are also used as promotional tools to increase product visibility. Evaluation of the activities shows an increase in knowledge and confidence among visually impaired SME operators in managing their businesses more independently and professionally. Synergy among the elements in the Pentahelix model has proven effective in supporting the development of SMEs for persons with disabilities toward sustainable economic independence. — Kegiatan pengabdian ini bertujuan untuk mendorong kemandirian ekonomi pelaku UMKM disabilitas netra di Kota Denpasar melalui pendekatan model Pentahelix. Model ini melibatkan lima unsur utama yaitu akademisi, pelaku bisnis, komunitas, pemerintah, dan media. Kegiatan ini dilaksanakan di UMKM Disabilitas Teratai, dengan metode berupa pra-survei, survey lapangan, pelaksanaan program, hingga evaluasi. Hasil temuan menunjukkan bahwa tantangan utama yang dihadapi mitra UMKM antara lain pencatatan keuangan yang belum terstruktur, kurangnya promosi, serta keterbatasan akses pasar. Akademisi berperan dalam penyusunan aplikasi akuntansi berbasis Microsoft Access untuk pencatatan transaksi sesuai standar SAK EMKM. Bisnis didorong melalui pelatihan dan pembuatan katalog online guna memperluas jangkauan pasar. Komunitas, melalui KUBE Gantari Jaya, memfasilitasi pelatihan dan bazzar produk. Pemerintah Kota Denpasar mendukung dengan penyediaan fasilitas dan legalisasi komunitas UMKM disabilitas. Pusaka Denpasar adalah platform kolaborasi yang melibatkan pemerintah, mitra, koperasi, dan UMKM untuk memajukan koperasi dan UMKM di kota Denpasar. Dinas Koperasi dan UMKM berperan sebagai fasilitator dalam penyediaan dokumen legal dan administrasi, sementara mitra kolaborasi berperan dalam pembinaan melalui berbagai program kerjasama. Media sosial dan media massa juga digunakan sebagai alat promosi untuk meningkatkan visibilitas produk. Evaluasi kegiatan menunjukkan peningkatan pengetahuan dan kepercayaan diri pelaku UMKM disabilitas netra dalam mengelola usahanya secara lebih mandiri dan profesional. Sinergi antar unsur dalam model Pentahelix terbukti efektif mendukung pengembangan UMKM disabilitas menuju kemandirian ekonomi yang berkelanjutan.